Geographical Information System Mapping For Potential Local Coastal Marine Case Study: Coastal Region Along The North Coast Java - Bambang Irawan; Arief Kusuma; Ari Pambudi; Yulhendri Yulhendri (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
The development of information technology is growing rapidly in many fields that provide convenience for every unit in every organizations, institutions and individuals in activities and efforts that will be undertaken to make the technology as an important element that influencing the business processes. Using the appropriate information technology will provide great benefits on any unit that implement them. In this study focusing on the design of a GIS (geographic information system) that is used to map the potential for coastal areas that will contribute for the best economic development in potential areas of the region that accordance with the state of the environment and support the resources of nature and local society. The right information will make it easier for investors to provide appropriate funding to support the region and to develop the local economy according to its ability.